Do Multinationals Transplant their Business Model? - Dalia Marin; Linda Rousova; Thierry Verdier (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2013)
What determines whether or not multinational firms transplant their mode of organisation to other countries? We embed the theory of knowledge hierarchies in an industry equilibrium model of monopolistic competition to examine how the economic environment may affect the decision of a multinational firm about transplanting its business organisation to other countries. We test the theory with original and matched parent and affiliate data on the internal organisation of 660 Austrian and German multinational firms and 2200 of their affiliate firms in Eastern Europe. We find that three factors stand out in promoting the multinational firm's decision to transplant the business model to the affiliate firm in the host country: a competitive host market, the corporate culture of the multinational firm, and when an innovative technology is transferred to the host country. These factors increase the respective probabilities of organisational transfer by 18.5 percentage points, 37, and 31 percentage points.
urn:nbn:de:bvb:19-epub-15115-9
Keywords: D23; F12; F23; F61; 330; organisational economics of multinational firms; trade and organisations; the theory of the firm; organisational transfer between countries